Nutrient and stoichiometry dynamics of decomposing litter in stream ecosystems: A global synthesis - Caleb J. Robbins; David W. P. Manning; Halvor M. Halvorson; Beth C. Norman; Rebecca A. Eckert; Ada Pastor; Allyn K. Dodd; Jérémy Jabiol; Elliot Bastias; Alice Gossiaux; Andrew S. Mehring (Ecology, 2023)
Decomposing organic matter forms a substantial resource base, fueling the biogeochemical function and secondary production of most aquatic ecosystems. However, detrital N (nitrogen) and P (phosphorus) dynamics remain relatively unexplored in aquatic ecosystems relative to terrestrial ecosystems, despite fundamentally linking microbial processes to ecosystem function across broad spatial scales. We synthesized 217 published time series of detrital carbon (C), N, P, and their stoichiometric ratios (C:N, C:P, N:P) from stream ecosystems to analyze the temporal nutrient dynamics of decomposing litter using generalized additive models. Model results indicated that detritus was a net source of N (irrespective of inorganic or organic form) to the environment, regardless of initial N content. In contrast, P sink/source dynamics were more strongly influenced by the initial P content, in which P‐poor litters were sinks for nutrients until these shifted to net P mineralization after ~40% mass loss. However, large variations surrounded both the N and P predictions, suggesting the importance of nonmicrobial factors such as fragmentation by invertebrates. Detrital C:N ratios converged and became more similar toward the end of the decomposition, suggesting predictable microbial functional effects throughout detrital ontogeny. C:P and N:P ratios also converged to some degree, but these model predictions were less robust than for C:N, due in part to the lower number of published detrital C:P time series. The explorations of environmental covariate effects were frequently limited by a few coincident covariate measurements across studies, but temperature, N availability, and P tended to accelerate the existing ontogenetic patterns in C:N. Our analysis helps to unite organic matter decomposition across aquatic–terrestrial boundaries by describing the basic patterns of elemental flows catalyzed by decomposition in streams, and points to a research agenda with which to continue addressing gaps in our knowledge of detrital nutrient dynamics across ecosystems.